Cognitive impairment in COVID-19: associations, pathogenesis and treatment questions - V. A. Golovacheva; G. R. Tabeeva; I. V. Kuznetsov (Неврология, нейропсихиатрия, психосоматика)
Cognitive impairment (CI) can be neurological symptoms or complications of coronavirus disease 2019 (COVID-19). Among  the pathogenetic mechanisms, the neurotropicity of the SARS- CoV-2 virus, endothelial dysfunction, coagulopathy, thrombus  formation, systemic inflammatory reaction, the consequences of mechanical ventilation and drug sedation are considered. Treatment strategies  for COVID-19 patients with CI have not yet been developed. The following tactics of patient management is advisable: prevention of  re-infection, assessment and correction of the emotional state,  treatment of cardiovascular diseases. The possibilities of  vinpocetine in the treatment of CI after COVID-19 are discussed.